Stuck in Slums: A Case Study of Slums in Islamabad, Pakistan - Samuel, Persis; Nisar, Muhammad Shemyal (European Scientific Journal, ESJ, 2021)
This paper focuses on finding answers to the reasons why people keep living in the slums and why they cannot get out of their precarious conditions. This paper looks into different reasons for people being stuck in slums from a religious perspective. Reasons for different religious groups being stuck in slums are not explored fully in the literature. The analysis draws on qualitative research with a sample of 53 semi-structured interviews conducted in 8 katchi abadis in Islamabad, Pakistan. The study shows that slums are nonhomogenous entities and are regarded as a living organism that provide safety, security, and a sense of belonging to some of the residents. The results revealed that both Christian and Muslim slum residents had different reasons for living in slums. There were not only inter-religious differences in the choice of living but intra religious differences had also been found. In the process, the paper highlights that most Christians lived in slums by choice due to strong social capital, with an exception of a few. On the other hand, Muslim slum residents lived in poverty which was a major reason most of the slum dwellers are stuck in slums. Policymakers should meet the needs of the people before implementing any policies. This is because relocation policies can bring misery to some of the slum dwellers. Finally, the paper demonstrated that slums play a pivotal role in the lives of the slum dwellers in keeping them.